COMPARATIVE ASSESSMENT OF REFLECTIVE ROOF COATINGS FOR REDUCING COOLING LOADS IN HOT–ARID CLIMATES: A TRANSIENT HEAT–BALANCE STUDY FOR BAGHDAD, IRAQ - Ehab Alaa Farhan; Hassanin Abd Ali Alfatlawy; Ali. K. Jasim (Antis-Publisher, 2026)
Objective: This study presents a model-based comparative assessment of five roof surface finishes—Standard Dark, White Reflective, Aluminum Metallic, Thermochromic, and Retro-Reflective—with respect to their ability to reduce cooling loads in buildings located in hot–arid climates. Method: A transient heat–balance model for a flat commercial roof is implemented in Python and driven by Typical Meteorological Year (TMY) data for Baghdad International Airport, Iraq. The model resolves hourly exterior surface temperatures using a nonlinear energy balance that accounts for absorbed solar radiation, wind-dependent convection, longwave exchange with the sky, and conduction into the conditioned interior. Results: For a 100 m² roof on a single-story commercial building maintained at 24 °C, the simulated annual roof-related conductive cooling load with a Standard Dark roof is 6268.2 kWh. Replacing this surface with a White Reflective coating reduces the annual roof-related conductive cooling load to 2888.7 kWh (53.9% savings for this specific roof and climate, near the upper end of ranges reported in the literature for reflective coatings in cooling-dominated regions). Assuming a typical cooling system coefficient of performance (COP) of 3.0, the corresponding electrical energy savings are approximately one-third of the thermal load reductions. Retro-Reflective and Thermochromic coatings yield annual roof-related conductive cooling loads of 3075.7 kWh (50.9% savings) and 3560.5 kWh (43.2% savings), respectively, while an Aluminum Metallic finish achieves 4562.8 kWh (27.2% savings). An economic evaluation incorporating a cooling system COP of 3.0 indicates that White Reflective coatings offer the shortest payback period (5.33 years) and the highest 10-year discounted net savings (134.7 USD) under current Iraqi electricity tariffs, followed by Aluminum Metallic, while Retro-Reflective and Thermochromic coatings show longer payback periods and negative net savings under the assumed conditions due to their higher initial costs relative to the electrical energy savings. Novelty: Advanced coating behaviors are represented through a temperature-dependent thermochromic reflectance function and a high-reflectance retro-reflective surface. A two-parameter sensitivity analysis demonstrates that both solar reflectance and thermal emittance exert strong, coupled influences on cooling load, with the lowest loads occurring for simultaneously high.